(untitled) (Journal of Forensic Medicine & Toxicology, 2015)
In the current trends of population growth, industrialization and rapid urbanization there has been an exponential growth in the motor vehicles on road, especially in developing countries like India. As per WHO reporting deaths per annum due to road traffic crashes is 1.2 million worldwide and 80000 in India. In the present study the most vulnerable age group was found to be between 40 to 59 years (54.3%) with a predominance of males (87%). Majority of the victims were having good educational back ground (52.2%), belonged to middle socio-economic groups (55.5%) and married (80.4%). Two wheeler riders sustained head injuries most commonly (60.86%) followed by pedestrians on the road (23.91%). Among the victims riding 2 wheelers helmet was not used in most of the cases (85.71%). The period of survival was between 1 to 7 days in maximum cases (52.17%). Most common fracture of vault observed was linear type (56.56%) and the most frequently affected part of skull was frontal bone (52.17%) followed by temporal bone (30.43%). The extra-axial haemorrhages observed in autopsy in all these cases revealed that subdural haemorrhage was most frequently encountered i.e. in 36 cases (78.26%) marginally followed by subarachnoid haemorrhage (73.91%).